2015
DOI: 10.1108/ijlls-07-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

Cross cultural analysis of an Iranian mathematics lesson

Abstract: Purpose – The purpose of this paper is to examine an Iranian mathematics lesson through the eyes of Japanese educators, and the critiques of Iranian teachers for raising the quality of teaching. In this paper, the Japanese lesson study process is considered as an approach to raising the quality of teaching. Design/methodology/approach – Qualitative methods including pre-lesson planning, peer observation of the lesson, post-lesson discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Expanding teachers' learning in a hybrid cross-cultural LS context Research has shown that analyzing RLs from cross-cultural LS can help researchers identify the cultural script of teaching and seek alternative ways of raising quality of teaching (Sarkar Arani, 2015, but what participating teachers learned from cross-cultural LS has been missing. Some cross-cultural LS research evidenced changes in participants' knowledge, but the learning mechanism has been largely unclear (Huang et al, 2021;Isoda et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expanding teachers' learning in a hybrid cross-cultural LS context Research has shown that analyzing RLs from cross-cultural LS can help researchers identify the cultural script of teaching and seek alternative ways of raising quality of teaching (Sarkar Arani, 2015, but what participating teachers learned from cross-cultural LS has been missing. Some cross-cultural LS research evidenced changes in participants' knowledge, but the learning mechanism has been largely unclear (Huang et al, 2021;Isoda et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Stigler and Hiebert (1999) argued that teaching is a cultural activity that is determined by the cultural script of teaching. Moreover, within the LS context, Sarkar Arani (2015Arani ( , 2016 developed a perspective for raising the quality of teaching through crosscultural lesson analysis which could help explicate the locally hidden cultural script of teaching and seek alternative effective practices from another culture. A few researchers explored how cross-cultural online LS could promote participating teachers' development of knowledge and digital literacy (Huang et al, 2021;Isoda et al, 2021), but learning processes and outcomes of online cross-culture LS are lacking rigorous and systematic investigation.…”
Section: Cross-cultural Lesson Study and Teacher Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…From the Japanese context of lesson study, lessons that give rise to “turns” are rich in “conversation, dialogue and discourse” (Shigematsu et al , 1963). This possibly refers to a deepening, changing of perspective, moving toward a new path, thinking of new methods, changing of view or paving the way for a new direction (Elliott, 2016; Lo, 2016; Sarkar Arani et al , 2014; Sarkar Arani, 2015, 2016b) in pedagogical improvement.…”
Section: Methodsmentioning
confidence: 99%
“…These four poem sections are known in Japanese as ki (introduction: provide learning task), sho (development: accumulate knowledge), ten (turn: expand dialogue) and ketsu (conclusion: internalise outcomes). The reason for applying this approach emerged from the findings of some of our recent studies (Sarkar Arani, 2015, 2016Sarkar Arani et al, 2014) which had innovatively applied this structure as a useful analytic framework for capturing the logic of the stages of teaching that occur in a lesson. It is widely accepted that the most important stage is ten.…”
Section: Comparative Lesson Analysismentioning
confidence: 99%